Mechanical Properties of Films Based on Blends of Starch-Coumarin Complex and Other Polymers Reinforced with Microcrystalline Cellulose - Permatasari, Amaliya Sita; Rachmawati, Rachmawati (Chimica et Natura Acta, 2025)
This research aimed to develop scented plastic materials based on cassava starch, coumarin, microcrystalline cellulose (MCC), and other polymers such as xanthan gum, karaya gum, gum arabic, poly(vinyl alcohol) (PVA), and poly(lactic acid). The films were made by solvent casting, focusing on using starch-coumarin (SC) complex as the base material. The SC complex was prepared by mixing starch and coumarin using water as a dispersion medium. The amount of coumarin was 5% (w/w), based on total weight of starch and coumarin. Several variations were used, such as types of plasticizers, stirring and sonication times to disperse MCC, types of added polymers, and the mass ratio between the added polymer and the starch-coumarin complex. The results showed that the films made of plasticizers 20% (w/w), consisting of poly(ethylene glycol) (PEG200) and glycerol with a mass ratio of 1:1, prepared by implementing 30 minutes stirring and 50 minutes sonication times of dispersing MCC of 4% (w/w), with the mass ratio of added polymer:complex of 1:2, resulted in the most optimum mechanical properties. Using this procedure and composition, added polymers of xanthan gum, karaya gum, and PVA produced homogenous films with tensile strength of 1.5-6.7 MPa, elongation of 9.5-189.7%, and Young’s modulus of 2.3-7.9 MPa. Amongst these added polymers, PVA showed the best compatibility in the blend, resulting in a film with a tensile strength of 3.9 MPa, an elongation of 189.7%, and Young’s modulus of 2.3.